Constituyentes del aceite esencial de Ocimum micranthum W. y estudio antimicrobiano - Fuerte Ruitón, César M. (1999)
The study of the chemistry composition of the volatil oil of Ocimum micranthum Wild was determinatged by chromatographies and spectronics methods, metil-eugenol (52.20%) was gottern like the principal component, in addition to cariofileno (15.67%), β-elemento (5,15%). The essential oil of Ocimum micranthum Wild were screened for antimicrobial activities (more sensibility over fungus), the agar overlay technique was applied over differents bacterials and fungus like this; Kleibsiella pneumonae, Staphylococcus aureus, Escherichia coli, Bacillus cereus, Shiguella sp., Aspergillus niger, aspergillus flavus, Aspergillus fumigatus and Penicllium sp.